Geriatric Chest Imaging: When and How to Image the Elderly Lung, Age-Related Changes, and Common Pathologies - J. Gossner; R. Nau (Radiology Research and Practice)
Even in a global perspective, societies are getting older. We think that diagnostic lung imaging of older patients requires special knowledge. Imaging strategies have to be adjusted to the needs of frail patients, for example, immobility, impossibility for long breath holds, renal insufficiency, or poor peripheral venous access. Beside conventional radiography, modern multislice computed tomography is the method of choice in lung imaging. It is especially important to separate the process of ageing from the disease itself. Pathologies with a special relevance for the elderly patient are discussed in detail: pneumonia, aspiration pneumonia, congestive heart failure, chronic obstructive pulmonary disease, the problem of overlapping heart failure and chronic obstructive pulmonary disease, pulmonary drug toxicity, incidental pulmonary embolism pulmonary nodules, and thoracic trauma.